Advancing sustainable agricultural productivity through structural adjustment and digitalization in China - Li, Mingwen; Feng, Fengcun; Nisar, Ubair; Khalid, Zainab (Frontiers in Sustainable Food Systems, 2025)
IntroductionSustainable agricultural productivity is a key priority for China as it navigates environmental challenges and growing food demand. Understanding the impact of agricultural structural adjustments, including crop-livestock integration, service-based agriculture, and digital transformation, on Green Total Factor Productivity (GTFP) is essential for formulating effective agricultural policies.MethodsThis study analyzes data from 1,743 counties in China spanning from 2003 to 2022. Using econometric models, we examine the relationship between agricultural structural adjustments and GTFP growth, focusing on the roles of technological progress, structural changes, and digitalization. The study accounts for regional variations in agricultural productivity.ResultsOur analysis finds that technological progress is the primary driver of GTFP growth. Agricultural structural changes, particularly crop-livestock integration and service-based models, contribute a “structural dividend,” enhancing sectoral efficiency and advancement. Interestingly, service-oriented models initially slow productivity but yield long-term benefits. Digital transformation significantly amplifies these positive effects. Regional analysis reveals that eastern and western regions benefit more from structural upgrades than central regions.DiscussionThese findings highlight the importance of designing policies tailored to local contexts, especially considering regional differences in agricultural productivity. The integration of digital technologies and service-oriented models plays a crucial role in advancing GTFP. Policy-makers should focus on promoting inclusive, sustainable, and technologically-driven agricultural development to meet China’s future food security needs.